A comparison for the maternal and perinatal outcomes between metformin and insulin in the treatment of gestational diabetes mellitus - Kassim, Nur Adzlinda (2016)
Background: Diabetes mellitus (DM) is an important complication of pregnancy which may carry adverse effects on both mother and fetus. While insulin is effective in controlling high blood glucose levels, otherwise resistant to diet and exercise management, several factors hinder its usage. Metformin has been found to be a convenient, cheap, effective and safe hypoglycaemic agent in some countries. It is possible that metformin will have similar beneficial effects among Malaysian pregnant women. Aim: The main aim of this study was to determine that metformin is an effective treatment for glycaemic control in the gestational diabetes mellitus (GDM) population in Malaysia as compared to insulin. It is also to assess the safety of these treatments by evaluating the maternal and fetal outcomes in GDM patients treated either with metformin or insulin. Methodology: A prospective, open label, randomized controlled study involving 99 pregnant women recruited between 12 – 32 weeks gestation, diagnosed with GDM. Patients were randomized to be either in the insulin group (n=48) or metformin group (n=51). Participants were followed-up throughout their pregnancy with a 2-weekly BSP monitoring till date of delivery. Mother and perinatal outcomes were followed-up till mother and baby were discharged from the ward postnatally. Both laboratory and clinical data were recorded and analyzed. Results: 98% and 95% of participants in the metformin and insulin groups respectively completed the study. The primary outcomes in comparing the differences of capillary blood glucose (BSP) levels between metformin group and insulin group shown that there is no significance difference between metformin group and insulin group at all different treatment periods. Maternal weight gains between both groups were no significantly different- at 8.8kg (±4.27) in metformin group to the 8.8kg (±3.43) insulin group (p > 0.950). The rates of maternal hypertension complications did not differ significantly between the two groups. Higher reported cases of urinary tract infection (UTI) in metformin group as in 30% while only 6.5% in the insulin group (p=0.003). Average birth weight in the metformin group [3.1kg (±0.26)] is similar to the insulin group [3.0kg (±0.48)]. No significance difference in neonatal morbidity; hypoglycemia, hyperbilirubinaemia or respiratory disorder, was observed between metformin and insulin group. Conclusion: Efficacy of metformin therapy was similar to insulin in giving good optimum glycaemic control in GDM women in Malaysia and carries similar low risk in term of maternal and perinatal outcomes. However, more studies with larger sample numbers, wider sample population are needed to collaborate these findings.